Thyroid Transcription Factor 1 Rescues PAX8/p300 Synergism Impaired by a Natural PAX8 Paired Domain Mutation with Dominant Negative Activity - Helmut Grasberger; Usanee Ringkananont; Paule LeFrancois; Marc Abramowicz; Gilbert Vassart; Samuel Refetoff (2005)
Mutations in the paired domain transcription factor PAX8 are a rare cause of congenital hypothyroidism due to thyroid dysgenesis. We identified a novel and unique PAX8 mutation segregating in seven affected members of a three-generations family. The mutation replaces an invariant serine residue within helix 2 of the paired DNA-binding domain for phenylalanine. The mutant protein (PAX8-S48F) does not induce the thyroglobulin promoter in nonthyroid cells, but displays almost half of wild-type PAX8 activity in thyroid cells. PAX8-S48F shows no defect in expression, nuclear targeting, or DNA binding and retains the ability to synergize with thyroid transcription factor 1 (TTF-1, NKX2.1). However, we found that in nonthyroid cells, the acetylation-independent synergism with the general transcriptional adaptor p300 is completely abrogated, suggesting that PAX8-S48F may be unable to efficiently recruit p300. Reconstitution experiments in nonthyroid cells reveal that TTF-1 can partially rescue PAX8-S48F/p300 synergism and thus reproduce the situation in thyroid cells. These functional characteristics result in a dominant negative effect of PAX8-S48F on coexpressed wild-type PAX8 activity, which is not observed in paired domain mutations with DNA binding defect. Our results describe the first dominant negative missense mutation in a paired domain and provide evidence for a crucial role of the p300 coactivator in mediating the functional synergism between PAX8 and TTF-1 in thyroid-specific gene expression.